Role of neutrophil gelatinase-associated lipocalin for early detection of acute kidney injury - Sanjeevani, Scienthia (Medknow Publications & Media Pvt Ltd, 2014)
Acute kidney injury (AKI) is characterized by abrupt or rapid decline of renal function and is usually associated with the development of serious complications as well as an independent risk of mortality in hospitalized patients. Emergency physicians play a critical role in recognizing early AKI, preventing iatrogenic injury, and reversing the course of AKI. Among the various available biomarkers for AKI, reliable and automated assay methods are commercially available for only cystatin-C and neutrophil gelatinase-associated lipocalin (NGAL). NGAL appears to be a promising marker for early detection of AKI and is likely to be adapted for wide-scale clinical use in patient management as a point-of-care test. Use of NGAL along with panel of other renal biomarkers can improve the rate of early detection of AKI. Large, multicenter studies demonstrate the association between biomarkers and hard end points such as need for renal replacement therapy (RRT), cardiovascular events, hospital stay, and death, independent of serum creatinine concentrations.